Effects of 4 weeks of foot exercise on subjective outcome and foot plantar pressure in elite adolescent dancers with hallux valgus: a pilot study - Zijian Liu; Yicheng Zhong; Shuo Chen; Hirofumi Tanaka; Yanshu Li; Hirofumi Katsutani; Takumi Okunuki; Hiroki Yabiku; Tsukasa Kumai (BMC, 2024)
Abstract Background Dancers have a higher prevalence of hallux valgus (HV) than the general population. However, no reports specifically addressing treatment strategies for HV in dancers, or their effectiveness have been published. This study aimed to determine the effects of 4 weeks of foot exercises on subjective clinical outcomes, the HV angle, and change of foot plantar pressure during specific dance techniques. Methods Thirteen female elite adolescent dancesport athletes (age: 16.4 ± 3.3 years) completed the program. The HV angle was measured based on foot photographs. Clinical assessments were performed using the visual analog scale for first metatarsophalangeal (1st MTP) joint pain, and the Foot and Ankle Outcome Score. The changes in plantar pressure during two dance techniques (demi-pointe and plié) were measured. The plantar pressure was measured in six areas of the foot. All of these parameters were compared before and after the intervention by using chi-square tests and Student's paired t-test (statistical significance: p < 0.05). Results The HV angle was significantly reduced from 20.1° to 15.4° after the intervention. Participants reported an average subjective completion rate of 70.3% ± 14.6% over 3 weeks, exhibiting no significant differences despite an apparent trend toward improvement. Significant changes were noted in 1st MTP joint pain and subjective outcomes, and toe function significantly improved in the "paper" movement. The foot-exercise program changed plantar pressure distribution during the demi-pointe and plié techniques, with increased hallux pressure and decreased 2nd-5th MTP joint pressure. Conclusions In elite adolescent dancesport athletes, 4 weeks of foot-exercise rehabilitation reduced the HV angle and improved in subjective outcome and function during the two dance techniques. Coaches should consider utilizing foot-exercise training programs in a dancer training program for HV.